Filter Bubble Trap: The Effect of TikTok Media on Language Use and Interaction Among Communication Science Students at UINSU - Pradana, Farhan; Efendi, Erwan (CV. ITTC INDONESIA, 2024)
This article aims to explore the impact of the filter bubble created by the social media algorithm of TikTok on the language use and social interactions of Communication Studies students at the State Islamic University of North Sumatra (UINSU). The urgency of this research lies in the increasing dominance of TikTok in students' daily lives and how this platform shapes their behavioral and communication patterns. This study employs a qualitative method with a field research approach. The primary data sources are 10 key informants selected through purposive sampling, while secondary data are derived from books, scholarly articles, and reports. Data collection techniques include interviews, observations, documentation, and literature study. Data analysis is carried out through data reduction, data display, and conclusion drawing, with the validity of the data tested using triangulation techniques. The findings indicate that the filter bubble phenomenon has varied effects on students. On one hand, some students feel that the filter bubble limits their views on social and cultural issues, while others find it helpful in obtaining relevant and beneficial information. Additionally, TikTok also influences the language usage of students, with some reporting an expansion in their vocabulary and an increase in creativity, although it also leads to the use of more colloquial and less formal language. The discussion highlights the importance of digital literacy and critical awareness in utilizing social media. These findings align with the filter bubble theory by Eli Pariser, which emphasizes the need for exposure to diverse views to avoid intellectual isolation. Overall, the research suggests that students should be trained to use social media wisely, enabling them to maximize its benefits without falling into the shackles of the filter bubble.